Effect of Sn/Cu thickness ratio on the transformation law of Cu6Sn5 to Cu3Sn in Sn/Cu interface during aging. (18th July 2018) - Zuozhu, Yin; Sun, Fenglian; Guo, Mengjiao
Abstract: The effect of Sn/Cu thickness ratio on the transformation rate of Cu3 Sn in Sn/Cu6 Sn5 /Cu3 Sn/Cu joint is investigated during different aging temperatures. The results show that Sn/Cu6 Sn5 /Cu3 Sn/Cu joint will transform into Sn/Cu6 Sn5 /Cu3 Sn joint as the Sn/Cu thickness ratio is 100/1. The thickness of Cu3 Sn ( δ 1 ) decreases linearly with increasing aging time and the consumption rate of Cu3 Sn ( ν 1 ) exhibites a parabolic relationship with aging temperature. This is due to the fact that the flux ratio ( r ) of the Cu atoms across the Cu3 Sn and Cu6 Sn5 layers is less than 1.2. Sn/Cu6 Sn5 /Cu3 Sn/Cu joint will transform into Cu/Cu3 Sn/Cu6 Sn5 joint as the Sn/Cu thickness ratio is 1/7.5. The thickness of Cu3 Sn ( δ 2 ) increases linearly with square root of aging time and the growth rate of Cu3 Sn ( ν 2 ) follows parabolic relationship with aging temperature. This is due to the fact that the value of r is more than 3.